A Comparative Study of Children with MIS-C between Admitted to the Pediatric Intensive Care Unit and Pediatric Ward: A One-Year Retrospective Study. (21st December 2021) - Kıymet, Elif; Böncüoğlu, Elif; Şahinkaya, Şahika; Cem, Ela; Çelebi, Miray Yılmaz; Düzgöl, Mine; Kara, Aybüke Akaslan; Arıkan, Kamile Ötiken; Vuran, Gamze Talay; Yılmazer, Murat Muhtar; Sandal, Özlem Saraç; Ağın, Hasan; et al.
Abstract: Objectives: This descriptive study aimed to compare the clinical and laboratory features of the children with the multisystem inflammatory syndrome in children (MIS-C), requiring pediatric intensive care unit (PICU), admission with the MIS-C patients who did not require PICU admission. Patients and methods: This study was conducted between March 2020 and February 2021 at the University of Health Sciences Dr. Behçet Uz Children's Hospital, a referral center for pediatric infectious diseases in the Aegean Region of Turkey. All hospitalized patients aged 18 years old or less with MIS-C according to the definition of the universal guidelines were included in the study. Data of the patients with the diagnosis of MIS-C were recorded and collected from the electronic medical records of the hospital. The data included demographic characteristics, presenting signs and symptoms, laboratory findings and clinical data. Results: A total of 58 patients with MIS-C were included in this study. Thirty-eight (65.5%) patients were male. The median age was 6 years (2 months–16 years). The patients admitted to PICU were 15 (25.9%). The rate of pulmonary involvement was 81.3% ( n = 13) in the PICU group. The median procalcitonin, C-reactive protein, erythrocyte sedimentation rate, D-Dimer and ferritin values were significantly higher in the PICU group compared to non-PICU group ( p < 0.001, p = 0.02, p < 0.001, p = 0.006 and p = 0.031). Conclusions: Besides the depressing cardiac functions reported before, the pulmonary involvement and signs of shock are important factors for PICU admission in children with MIS-C.